2017
DOI: 10.1175/mwr-d-16-0411.1
|View full text |Cite
|
Sign up to set email alerts
|

A Climatology of Central American Gyres

Abstract: Central American gyres (CAGs) are large, closed, cyclonic circulations that occur during the rainy season (May–November), which can yield exceptional rainfall leading to catastrophic flooding and large societal impacts. A reanalysis-based climatology of CAGs is developed from an algorithm that distinguishes CAG cases from other systems. This algorithm identified CAG cases based on circulation intensity, a broad radius of maximum winds, and the existence of closed, Earth-relative, cyclonic flow. Based on these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…The RMW (Fig. 4a) has a fairly large spread early in the forecast, as a small inner core developed within a broader, gyre-like circulation (e.g., Papin et al 2017); however, after the first ;24 h, the variability decreases, and the observed RMW is close to the median of the ensemble envelope. Interestingly, the RMW remains relatively constant after hour 36 in both the model and observations.…”
Section: ) Wind Radiimentioning
confidence: 99%
See 1 more Smart Citation
“…The RMW (Fig. 4a) has a fairly large spread early in the forecast, as a small inner core developed within a broader, gyre-like circulation (e.g., Papin et al 2017); however, after the first ;24 h, the variability decreases, and the observed RMW is close to the median of the ensemble envelope. Interestingly, the RMW remains relatively constant after hour 36 in both the model and observations.…”
Section: ) Wind Radiimentioning
confidence: 99%
“…Hurricane Michael was the strongest TC of the 2018 Atlantic hurricane season. The TC formed over the northwestern Caribbean Sea from a Central American gyre (e.g., Papin et al 2017) and moved into the Gulf of Mexico (GoM). It was a TC that developed and underwent rapid intensification (RI, a change in maximum wind speed of 30 kt (15 m s 21 ) or more in a 24-h period, Kaplan et al 2010) in a moderate-to high-shear environment.…”
Section: A Case Descriptionmentioning
confidence: 99%
“…The explanation is that as TCs graze the coast or make landfall, the friction gradient between the land and the sea could promote convection and then generate scattered rainbands on the land-interacting side, which results in a more enclosed pattern (Xu et al, 2014). Particularly over the western Gulf of Mexico, interactions with complex topography (e.g., the mountains of eastern Mexico) (Figure 2a), as well as the complex interaction between abundant moisture and convergence due to the gyre (Papin et al, 2017), have a major impact on the small, dispersive and relatively enclosed storm rainfall patterns. All of these results point to the importance of analysing the regional variation in storm responses to environmental factors.…”
Section: Discussion Of Gwr Resultsmentioning
confidence: 99%
“…Storms over the Gulf that are weaker are more susceptible to being altered by upper‐level systems (e.g., Tropical Storm Arlene in 2011) (Beven, 2012). In particular, TCs frequently occur over Central America in conjunction with Central American Gyres, which are large, low‐level circulations and upper‐tropospheric anticyclone or trough structures coupled with anomalous moisture, which can result in torrential rainfall over portions of Central America (Papin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…La TT Cristóbal se formó a finales de mayo de 2020 a partir de la depresión tropical No. 3 (SMN, 2020b), en un área muy extensa de bajas presiones, de circulación ciclónica con convección embebida, en la zona que se le llama Giro Centroamericano (Papin et al, 2017), este sistema, aunque categorizado por su circulación (ciclónico o anticiclónica) en la alta troposfera en coincidencia con circulación ciclónica en superficie que ocasiona lluvias abundantes, debido a la convección profunda que presenta asociada a este vórtice, que se localiza en las cercanías de Centro América (Aldinger and Stapler,1998;American Meteorological Society 2016). Desde el 31 de mayo, de acuerdo con los modelos que se manejan en el Centro Nacional de Huracanes de Miami (NHC por sus siglas en inglés) se pronosticaba su fortalecimiento hasta alcanzar la categoría de TT (NOAA, 2020e); sin embargo, lo hizo hasta el 2 de junio para convertirse en la TT más prematura, con la letra "C" que afectaría a la Península de Yucatán (NHC-NOAA, 2020).…”
Section: La Tt Cristóbalunclassified